2007
DOI: 10.1097/qai.0b013e318149297d
|View full text |Cite
|
Sign up to set email alerts
|

Lessons From a Multisite International Trial in the Caribbean and South America of an HIV-1 Canarypox Vaccine (ALVAC-HIV vCP1452) With or Without Boosting With MN rgp120

Abstract: The observation of disappointing immunogenicity in this and a parallel domestic study has informed future vaccine development. Equally important, challenges to doing an integrated trial across countries, cultures, languages, and differing at-risk populations were overcome. The identification of specific safety, ethical, logistic, and immunological issues in this trial established the foundation for current larger international studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 33 publications
0
25
0
Order By: Relevance
“…For example, the ALVAC HIV-1 vaccine in humans elicited HIV-1-specific CD8 + T cell responses in less than 25% of normal volunteers (8)(9)(10). Similarly, MVA expressing the GAG protein (consensus of HIV-1 clade A) and several immunodominant CD8 + T cell epitopes resulted in responses detectable in only 17% of individuals (34).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the ALVAC HIV-1 vaccine in humans elicited HIV-1-specific CD8 + T cell responses in less than 25% of normal volunteers (8)(9)(10). Similarly, MVA expressing the GAG protein (consensus of HIV-1 clade A) and several immunodominant CD8 + T cell epitopes resulted in responses detectable in only 17% of individuals (34).…”
Section: Discussionmentioning
confidence: 99%
“…These include modified VACV Ankara (MVA) (14), a variant of Lister strain LC16m8; ACAM1000/2000, derived from New York City Board of Health strain NYCBOH; the highly deleted Copenhagen VACV strain derivative NYVAC; and attenuated canarypox virus (ALVAC). Although some vectors given by certain routes might result in strong CD8 + T cell responses, the literature also suggests there is variability in the levels of CD8 + T cell immunity, raising the question of what determines induction of optimal CD8 + T cell responses (2,(7)(8)(9)(10)(15)(16)(17). Using several clinically relevant natural and recombinant VACV variants, we show here a quantitative difference in CD8 + T cell immunity elicited depending on the virus and immunization route, with only the most virulent VACVs promoting protective populations of memory CD8 + T cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that ALVAC HIV-1 vaccines are safe [9], and unlike adenovirus vectors, may not be limited by pre-existing anti-vector immunity [10,11]. However, ALVAC immunogenicity in humans is low, eliciting HIV-1-specific cytotoxic CD8 + T cell (CTL) responses in less than 25% of normal volunteers in clinical studies [12][13][14], implying that further efforts need to be done to improve the immunogenicity of current canarypox HIV-1 vaccines.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, a different study showed that tetramer-positive CD8 ϩ T-cell responses were induced at mucosal sites by live attenuated poxvirus NYVAC encoding HVTN 203), demonstrated by IFN-␥ ELISPOT assays, were observed in less than 36% of the vaccinees; therefore, the planned phase III trial (HVTN 501) was cancelled. Results from another phase II trial, outside of the United States, which tested ALVAC with or without a rgp120 booster (HVTN 026), did not show a difference in cellular immunity between the vaccinated and placebo groups, as measured by IFN-␥ ELISPOT assays, lymphocyte proliferation assays, or Cr release assays (35). Increasing the dose of the ALVAC vector (HVTN 039) or the addition of lipopeptides (HVTN 042) did not enhance the number of responders, 5 of 52 and 3 of 77, respectively (37).…”
Section: Poxvirus Vectorsmentioning
confidence: 99%